2021
DOI: 10.15358/0344-1369-2021-4-28
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Consumers' Purchase Channel Preference in Omni-Channel Retailing

Abstract: Mobile technology and digitalisation put pressure on retailers to engage in omni-channel retailing. However, to avoid cannibalisation and create synergies, channels must differ and provide a unique service offer to the consumer. Indeed, little is known about what constitutes consumers’ channel preference in omni-channel environments. Thus, the present study evaluates consumers’ purchase channel preference considering benefits and costs. Besides, the role of channel experience and product category is estimated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The brick-and-mortar store environment facilitates customers’ immediate and generally reassuring assessment of these risks. Accordingly, perceived risks of offline channels, such as privacy or security concerns, appear to have no significant effect on attitudes toward purchasing via offline channels (Eckl and Lingenfelder 2021 ; Wang et al 2016 ). The perception of risks relating to online channels, by contrast, results directly in a decrease in online channel use (Lee and Jung 2020 ; Madden et al 2017 ; Montoya-Weiss et al 2003 ) and greater use of alternative channels such as brick-and-mortar stores (Chiu et al 2011 ; Kukar-Kinney and Close 2010 ).…”
Section: Analysis and Findingsmentioning
confidence: 99%
See 4 more Smart Citations
“…The brick-and-mortar store environment facilitates customers’ immediate and generally reassuring assessment of these risks. Accordingly, perceived risks of offline channels, such as privacy or security concerns, appear to have no significant effect on attitudes toward purchasing via offline channels (Eckl and Lingenfelder 2021 ; Wang et al 2016 ). The perception of risks relating to online channels, by contrast, results directly in a decrease in online channel use (Lee and Jung 2020 ; Madden et al 2017 ; Montoya-Weiss et al 2003 ) and greater use of alternative channels such as brick-and-mortar stores (Chiu et al 2011 ; Kukar-Kinney and Close 2010 ).…”
Section: Analysis and Findingsmentioning
confidence: 99%
“…The perception of risks relating to online channels, by contrast, results directly in a decrease in online channel use (Lee and Jung 2020 ; Madden et al 2017 ; Montoya-Weiss et al 2003 ) and greater use of alternative channels such as brick-and-mortar stores (Chiu et al 2011 ; Kukar-Kinney and Close 2010 ). However, arising from the COVID-19 pandemic and associated threats such as danger of infection, other channel risks like human contact gain importance and consumers´ channel choice becomes health-related behavior (Eckl and Lingenfelder 2021 ; Wang et al 2021a ). For instance, Wang et al ( 2021a ) showed that perceived susceptibility to COVID-19 combined with the perceived severity of the virus positively influences the value of channels that do not involve human contact.…”
Section: Analysis and Findingsmentioning
confidence: 99%
See 3 more Smart Citations